Removal of shells in palm kernel cake via static cling and electrostatic separation (Journal of Biochemistry, Microbiology and Biotechnology, 2015)
Palm kernel cake (PKC), a by-product of the palm oil industry is limited in its use as a feed ingredient for poultry due to its high fibre and lignin content. The presence of these antinutritive components is the result of shells contaminating the by-product. The nutritive value of PKC has to be improved in order to increase its inclusion rate in poultry diet. In this study, PKC was subjected to a separation method using static cling and electrostatic separation to removethe shells present in PKC. Response surface methodology based on Box-Behnken design was used to optimize the separation method with moisture content (8 to 18%), particle size distribution (0.5 to 2.5 mm) and feed rate (20 to 200 g/min) as the independent variables evaluated. According to the regression coefficients and significance of the quadratic polynomial model, the optimum separation parameters were as follows: 13% PKC moisture content;